2004
DOI: 10.1038/nm1109
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nebulized nitrite is a hypoxia-sensitive NO-dependent selective pulmonary vasodilator

Abstract: The blood anion nitrite contributes to hypoxic vasodilation through a heme-based, nitric oxide (NO)-generating reaction with deoxyhemoglobin and potentially other heme proteins. We hypothesized that this biochemical reaction could be harnessed for the treatment of neonatal pulmonary hypertension, an NO-deficient state characterized by pulmonary vasoconstriction, right-to-left shunt pathophysiology and systemic hypoxemia. To test this, we delivered inhaled sodium nitrite by aerosol to newborn lambs with hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
211
0
8

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(231 citation statements)
references
References 27 publications
11
211
0
8
Order By: Relevance
“…has shown efficacy in reducing pulmonary pressures and preventing right ventricular hypertrophy (19)(20)(21). More recent work has demonstrated that acute IV administration of nitrite improves exercise capacity in patients with HFpEF, a group at high risk for secondary (Group 2) PH (22).…”
Section: Methodsmentioning
confidence: 99%
“…has shown efficacy in reducing pulmonary pressures and preventing right ventricular hypertrophy (19)(20)(21). More recent work has demonstrated that acute IV administration of nitrite improves exercise capacity in patients with HFpEF, a group at high risk for secondary (Group 2) PH (22).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of nitrite-dependent oxidation of deoxyhemoglobin (deoxyHb) 2 under anaerobic conditions, and its physiological potential in hypoxic vasodilation has recently been established (3)(4)(5). However, the mechanism of reaction between oxyhemoglobin (oxyHb) and nitrite has not yet been fully elucidated.…”
mentioning
confidence: 99%
“…In particular, being the main source of the drinking water, ground waters are characterized worldwide as having increased nitrate concentration [6]. Being extensively used in industrial [7] and biomedical applications [8][9][10], nitrite is one of the most reactive substances in the nitrogen cycle and has a significant toxicity for humans, being the main cause of blue baby syndrome [11]. Consumed nitrate is also reduced to nitrite by enteric bacteria, which might subsequently lead to serious health risks [12,13].…”
Section: Introductionmentioning
confidence: 99%